2019
DOI: 10.4236/jmp.2019.103025
|View full text |Cite
|
Sign up to set email alerts
|

Generating Compatibility Conditions and General Relativity

Abstract: The search for generating compatibility conditions (CC) for a given operator is a very recent problem met in General Relativity in order to study the Killing operator for various standard useful metrics (Minkowski, Schwarschild and Kerr). In this paper, we prove that the link existing between the lack of formal exactness of an operator sequence on the jet level, the lack of formal exactness of its corresponding symbol sequence and the lack of formal integrability (FI) of the initial operator is of a purely hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…However, it can be shown that, on Kerr, there is no second order operator L with symbol σ p (ϑ 2 ) such that LK 0 = 0, and hence K 0 fails to be involutive. It was rightly noted in [29,30] that constructing a full compatibility operator for an involutive version of K 0 is much easier. However, we point out that our K 0 is tied to the fixed notion of gauge symmetry and gauge invariance in linearized gravity, hence we are not free to replace it with its involutive prolongation.…”
Section: Counting Invariantsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be shown that, on Kerr, there is no second order operator L with symbol σ p (ϑ 2 ) such that LK 0 = 0, and hence K 0 fails to be involutive. It was rightly noted in [29,30] that constructing a full compatibility operator for an involutive version of K 0 is much easier. However, we point out that our K 0 is tied to the fixed notion of gauge symmetry and gauge invariance in linearized gravity, hence we are not free to replace it with its involutive prolongation.…”
Section: Counting Invariantsmentioning
confidence: 99%
“…Nevertheless, this paper is the first to fully demonstrate completeness for a set of gauge invariants for the Kerr spacetime. See [29,30] for work on related problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ad  is parametrizing the operator ( ) However, we shall discover that the dimension 4 n = , which is particularly "fine" for the classical Killing sequence, is particularly "bad" for the conformal Killing sequence, a result not known after one century because it cannot be understood without using the Spencer δ-cohomology in the following commutative diagram which is explaining therefore what we shall call the "Lanczos secret". Following ( [21]) and the fact that the two central vertical δ-sequences are exact, this diagram allows to construct the Bianchi operator 2 1 2 : F F →  as generating CC for the Riemann operator…”
Section: Riemann/lanczos Problemmentioning
confidence: 99%
“…REMARK 1.1.4: As long as the Prolongation/Projection (PP) procedure has not been achieved in order to get an involutive system, nothing can be said about the CC (fine examples can be found in [6] and the recent [10]). A proof that the second order system defined by Einstein equations is involutive has been given by J. Gasqui in 1982 but this paper cannot be applied to the minimum parametrizations that need specific δ -regular coordinates as we shall see [11].…”
Section: System Theorymentioning
confidence: 99%